Positively uncivilized - Priest, Rena (Raven Chronicles Press, 2025)
From an Indigenous perspective, Positively Uncivilized examines the impact of human inhabitants on the planet earth. Alongside personal accounts of the deterioration of salmon populations in the Pacific Northwest and the loss of Indigenous history, the twelve essays in this collection emphasize the necessity of community to overcome the damage done by human socioeconomic and political systems designed to isolate and shame those vulnerable to those unfair systems.